Evolution of Technology Management in Human Resource Development: a Qualitative Perspective on Start-Up Companies - Sukiman; Pering, I Gede Arya; Muhammad, A Fadel; Razak, Annisa Zhalila; Rostini (Economics and Business Journal (ECBIS), 2025)
This study investigates the role of technology management in human resource management (HRM) within start-up companies in Indonesia. Focusing on start-ups that have been operating for at least three years and employ a minimum of 20 personnel, the research utilizes a qualitative descriptive approach. Primary data was collected through in-depth interviews with HR managers, company executives, and employees, while secondary data was sourced from company documents and participatory observation. The findings show that the adoption of technology, particularly Human Resource Management Systems (HRMS) and Learning Management Systems (LMS), has improved HR processes, including recruitment, training, and performance management. However, challenges remain, such as digital literacy issues, cost constraints, and the misalignment of technology with organizational culture. While technology enhances operational efficiency, it cannot replace essential face-to-face interactions that contribute to a strong organizational culture. The study suggests that start-ups must customize technology solutions to better align with their specific needs and culture. This research provides valuable insights into the integration of technology in HRM and offers recommendations for overcoming the challenges start-ups face in leveraging technology effectively